PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING: (Studi Kasus Di UPT Rumah Susun Kota Magelang) (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
This research aims to determine whether there is a direct influence between compensation, work discipline and work motivation on employee performance and researchers also want to know the influence of work motivation in mediating compensation and work discipline with employee performance at UPT Rumah Susun Magelang City. The research method used is a quantitative method. The research subjects were 38 employees at the UPT Rumah Susun Magelang City. The data collection technique used is a questionnaire that has been tested for validation and reliability, then tested using path analysis. The variables in this research are compensation (X1), work discipline (X2), employee performance (Y) and work motivation (Z). Data were analyzed using SPSS version 25 software. Based on the results of research tests conducted, it shows that the compensation variable does not significantly influence employee performance variables, the work discipline variable significantly influences employee performance variables, the work motivation variable does not significantly influence employee performance variables, the compensation variable does not significantly influence employee performance variables. Work motivation, and work discipline variables have a significant effect on work motivation variables. Meanwhile, for mediation, work motivation variables cannot mediate compensation variables on employee performance variables, and work motivation also cannot mediate work discipline variables on employee performance variables.
Keywords: compensation; work discipline; employee performance and work motivation